Pirates of the Caribbean. Dead men tell no tales [videorecording (DVD)] - Roenning, Joachim, 1972-; Sandberg, Espen; Depp, Johnny; Bardem, Javier, 1969-; Rush, Geoffrey, 1951- (Walt Disney Studios Home Entertainment, 2017)
Captain Jack Sparrow searches for the Trident of Poseidon.